2002
DOI: 10.1046/j.1442-9071.2002.00554.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of daunorubicin in inhibiting proliferative vitreoretinopathy after retinal detachment surgery

Abstract: Daunorubicin may be a useful drug in inhibiting proliferative vitreoretinopathy after surgery for primary rhegmatogenous retinal detachment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 12 publications
0
17
0
4
Order By: Relevance
“…6 Although the antifibroblastic action of DNR has been known for over two decades, its safety in various ophthalmic surgeries has been demonstrated in the last decade. DNR has increasingly been used to improve the success rate of ocular surgeries, including strabismus surgery, 7 pterygium surgery, 8 retinal detachment surgery, 9 and in the prevention of PCO following cataract extraction. 10,11 Dadeya et al 16,6 evaluated the safety and efficacy of intraoperative 0.02% DNR in strabismus surgery and pterygium surgery.…”
Section: Daunorubicinmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Although the antifibroblastic action of DNR has been known for over two decades, its safety in various ophthalmic surgeries has been demonstrated in the last decade. DNR has increasingly been used to improve the success rate of ocular surgeries, including strabismus surgery, 7 pterygium surgery, 8 retinal detachment surgery, 9 and in the prevention of PCO following cataract extraction. 10,11 Dadeya et al 16,6 evaluated the safety and efficacy of intraoperative 0.02% DNR in strabismus surgery and pterygium surgery.…”
Section: Daunorubicinmentioning
confidence: 99%
“…They concluded that DNR seemed to be effective to suppress reproliferation, but that care should be taken to avoid postoperative complications. 9,[22][23][24][25] Some workers 10,11 have performed research into use of DNR as an agent for preventing PCO. They noted that DNR could effectively inhibit the proliferation of human lens epithelial cells in vitro at the concentration of 0.5 mg/ml, almost reaching the greatest effect at the concentration of 7.5 mg/ml.…”
Section: Daunorubicinmentioning
confidence: 99%
See 1 more Smart Citation
“…Kumar et al [57] recently reported the efficacy of an intravitreal injection of DAU before conclusion of the vitrectomy. However, Esser et al [58] showed that adjuvant intravitreal DAU induces multi-drug resistance (MDR) and proposed that reproliferation in DAU pre-treated patient probably necessitates cotreatment with inhibitors such as verapamil or administration of antiproliferative drug which acts in a MDR-independent fashion.…”
Section: Drug Treatment Of Pvrmentioning
confidence: 97%
“…Cependant, cet adjuvant n'a pas amélioré le pronostic fonctionnel et anatomique (réapplication rétinienne en 1 chirurgie dans 65 % vs 54 %, groupe contrôle). Une autre étude [52] a montré un meilleur succès anatomique chez les patients ayant bénéfi-cié du traitement par daunomycine. Cet adjuvant n'est pas actuellement utilisé couramment.…”
Section: Daunomycineunclassified